2008
DOI: 10.1210/jc.2007-2368
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroperoxidase and Antithyroglobulin Antibodies in a Five-Year Follow-Up Survey of Populations with Different Iodine Intakes

Abstract: Subjects who were TPOAb and TgAb positive at baseline developed thyroid dysfunctions more frequently than seronegative subjects. High iodine intake was a risk factor for developing hypothyroidism in antibody-positive subjects. A constant exposure to excessive iodine intake increased the incidence of positive TgAb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
97
5
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(128 citation statements)
references
References 24 publications
22
97
5
4
Order By: Relevance
“…Even excluding patients with high thyroid antibodies, serum TSH concentration is an independent risk factor of DTC, suggesting the increasing risk of DTC in patients with TSH in the upper end of normal or markedly elevated level is unlikely to be solely due to increased antithyroid antibody levels. This demonstrates the real association between TSH and malignancy, given the well known influence of anti-thyroid antibodies on TSH [21,22]. Moreover, our data show that higher TSH in patients with DTC occurs independent of age, which is also an important influencing factor on serum TSH levels.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Even excluding patients with high thyroid antibodies, serum TSH concentration is an independent risk factor of DTC, suggesting the increasing risk of DTC in patients with TSH in the upper end of normal or markedly elevated level is unlikely to be solely due to increased antithyroid antibody levels. This demonstrates the real association between TSH and malignancy, given the well known influence of anti-thyroid antibodies on TSH [21,22]. Moreover, our data show that higher TSH in patients with DTC occurs independent of age, which is also an important influencing factor on serum TSH levels.…”
Section: Discussionsupporting
confidence: 69%
“…The reference range, intra-assay and inter-assay coefficients of variation were 0.3-4.8 mIU/L [21], 4.9% and 5.2%, respectively, for TSH. Serum TPOAb exceeding a level of 50 KIU/L and/or TgAb exceeding a level of 40 KIU/L were considered as high serum autoantibody values [22]. The intra-assay and inter-assay coefficients of variations for TPOAb and TgAb were less than 8.5%.…”
Section: Thyroid Profilesmentioning
confidence: 99%
“…4,5,15 Furthermore, the current study detected a significantly greater serum median TSH concentration in tparticipants who were positive for thyroid autoantibodies compared with those who were negative. A significant association was demonstrated between an elevated TSH level and the presence of thyroid autoantibodies.…”
Section: Discussionsupporting
confidence: 54%
“…Li et al reported that constant exposure to an excessive iodine intake increased the incidence of positive TgAb, and only TgAb-positive subjects from areas with relatively high iodine intakes were more likely to develop hypothyroidism than only TPOAb-positive subjects [20]. The average dietary iodine intake due to the ingestion of seaweeds is 1.2 mg/day in Japan [21].…”
Section: Acknowledgementmentioning
confidence: 99%